Perancangan Sistem Informasi Kinerja Dosen Sebagai Acuan Kenaikan Level - Encep Supriatna (INTERNAL (Information System Journal), 2021)
Evaluation of lecturer performance is currently still done manually by three parts, namely assessment of learning performance by study programs, assessment of research and community service by LPPM, and overall assessment by the rector. Because it doesn't use a database, data from one section cannot be accessed by other sections, so each section must repeat the same transaction, besides that lecturers must make copies of documents to be submitted to each section that requires it, this is considered inefficient. For this reason, it is necessary to make a lecturer performance information system so that the lecturer's performance appraisal activity becomes more effective. Another benefit of a computerized system is that it can minimize subjectivity in the assessment process, the assessment becomes transparent and lecturers can monitor the results of their performance whenever needed. The method used in developing this system is the User Experience Design Process method, which includes product devintion, research, analysis, design, implementation. Data was collected by observation, interviews, and literature study. The system modeling uses the Unified Modeling Language (UML). the tools used are use case diagrams, activity diagrams, sequence diagrams and class diagrams. The implementation uses the PHP and HTML programming languages ??and MySQL as the database. The results of this study can integrate data on the performance assessment process of lecturers from different departments, the information generated from each process and its supporting documents can be accessed by all privately related departments, and the subjectivity of the assessment team can be minimized.